src/HOL/Ln.thy
author wenzelm
Fri Jan 14 15:44:47 2011 +0100 (2011-01-14)
changeset 41550 efa734d9b221
parent 40864 4abaaadfdaf2
child 41959 b460124855b8
permissions -rw-r--r--
eliminated global prems;
tuned proofs;
avigad@16959
     1
(*  Title:      Ln.thy
avigad@16959
     2
    Author:     Jeremy Avigad
avigad@16959
     3
*)
avigad@16959
     4
avigad@16959
     5
header {* Properties of ln *}
avigad@16959
     6
avigad@16959
     7
theory Ln
avigad@16959
     8
imports Transcendental
avigad@16959
     9
begin
avigad@16959
    10
avigad@16959
    11
lemma exp_first_two_terms: "exp x = 1 + x + suminf (%n. 
nipkow@40864
    12
  inverse(fact (n+2)) * (x ^ (n+2)))"
avigad@16959
    13
proof -
nipkow@40864
    14
  have "exp x = suminf (%n. inverse(fact n) * (x ^ n))"
wenzelm@19765
    15
    by (simp add: exp_def)
nipkow@40864
    16
  also from summable_exp have "... = (SUM n::nat : {0..<2}. 
nipkow@40864
    17
      inverse(fact n) * (x ^ n)) + suminf (%n.
nipkow@40864
    18
      inverse(fact(n+2)) * (x ^ (n+2)))" (is "_ = ?a + _")
avigad@16959
    19
    by (rule suminf_split_initial_segment)
avigad@16959
    20
  also have "?a = 1 + x"
avigad@16959
    21
    by (simp add: numerals)
avigad@16959
    22
  finally show ?thesis .
avigad@16959
    23
qed
avigad@16959
    24
avigad@16959
    25
lemma exp_tail_after_first_two_terms_summable: 
nipkow@40864
    26
  "summable (%n. inverse(fact (n+2)) * (x ^ (n+2)))"
avigad@16959
    27
proof -
avigad@16959
    28
  note summable_exp
avigad@16959
    29
  thus ?thesis
avigad@16959
    30
    by (frule summable_ignore_initial_segment)
avigad@16959
    31
qed
avigad@16959
    32
avigad@16959
    33
lemma aux1: assumes a: "0 <= x" and b: "x <= 1"
nipkow@40864
    34
    shows "inverse (fact ((n::nat) + 2)) * x ^ (n + 2) <= (x^2/2) * ((1/2)^n)"
avigad@16959
    35
proof (induct n)
nipkow@40864
    36
  show "inverse (fact ((0::nat) + 2)) * x ^ (0 + 2) <= 
avigad@16959
    37
      x ^ 2 / 2 * (1 / 2) ^ 0"
nipkow@23482
    38
    by (simp add: real_of_nat_Suc power2_eq_square)
avigad@16959
    39
next
avigad@32038
    40
  fix n :: nat
nipkow@40864
    41
  assume c: "inverse (fact (n + 2)) * x ^ (n + 2)
avigad@16959
    42
       <= x ^ 2 / 2 * (1 / 2) ^ n"
nipkow@40864
    43
  show "inverse (fact (Suc n + 2)) * x ^ (Suc n + 2)
avigad@16959
    44
           <= x ^ 2 / 2 * (1 / 2) ^ Suc n"
avigad@16959
    45
  proof -
nipkow@40864
    46
    have "inverse(fact (Suc n + 2)) <= (1/2) * inverse (fact (n+2))"
avigad@16959
    47
    proof -
avigad@16959
    48
      have "Suc n + 2 = Suc (n + 2)" by simp
avigad@16959
    49
      then have "fact (Suc n + 2) = Suc (n + 2) * fact (n + 2)" 
avigad@16959
    50
        by simp
avigad@16959
    51
      then have "real(fact (Suc n + 2)) = real(Suc (n + 2) * fact (n + 2))" 
avigad@16959
    52
        apply (rule subst)
avigad@16959
    53
        apply (rule refl)
avigad@16959
    54
        done
avigad@16959
    55
      also have "... = real(Suc (n + 2)) * real(fact (n + 2))"
avigad@16959
    56
        by (rule real_of_nat_mult)
avigad@16959
    57
      finally have "real (fact (Suc n + 2)) = 
avigad@16959
    58
         real (Suc (n + 2)) * real (fact (n + 2))" .
nipkow@40864
    59
      then have "inverse(fact (Suc n + 2)) = 
nipkow@40864
    60
         inverse(Suc (n + 2)) * inverse(fact (n + 2))"
avigad@16959
    61
        apply (rule ssubst)
avigad@16959
    62
        apply (rule inverse_mult_distrib)
avigad@16959
    63
        done
nipkow@40864
    64
      also have "... <= (1/2) * inverse(fact (n + 2))"
avigad@16959
    65
        apply (rule mult_right_mono)
avigad@16959
    66
        apply (subst inverse_eq_divide)
avigad@16959
    67
        apply simp
avigad@16959
    68
        apply (rule inv_real_of_nat_fact_ge_zero)
avigad@16959
    69
        done
avigad@16959
    70
      finally show ?thesis .
avigad@16959
    71
    qed
avigad@16959
    72
    moreover have "x ^ (Suc n + 2) <= x ^ (n + 2)"
avigad@16959
    73
      apply (simp add: mult_compare_simps)
wenzelm@41550
    74
      apply (simp add: assms)
avigad@16959
    75
      apply (subgoal_tac "0 <= x * (x * x^n)")
avigad@16959
    76
      apply force
avigad@16959
    77
      apply (rule mult_nonneg_nonneg, rule a)+
avigad@16959
    78
      apply (rule zero_le_power, rule a)
avigad@16959
    79
      done
nipkow@40864
    80
    ultimately have "inverse (fact (Suc n + 2)) *  x ^ (Suc n + 2) <=
nipkow@40864
    81
        (1 / 2 * inverse (fact (n + 2))) * x ^ (n + 2)"
avigad@16959
    82
      apply (rule mult_mono)
avigad@16959
    83
      apply (rule mult_nonneg_nonneg)
avigad@16959
    84
      apply simp
avigad@16959
    85
      apply (subst inverse_nonnegative_iff_nonnegative)
huffman@27483
    86
      apply (rule real_of_nat_ge_zero)
avigad@16959
    87
      apply (rule zero_le_power)
huffman@23441
    88
      apply (rule a)
avigad@16959
    89
      done
nipkow@40864
    90
    also have "... = 1 / 2 * (inverse (fact (n + 2)) * x ^ (n + 2))"
avigad@16959
    91
      by simp
avigad@16959
    92
    also have "... <= 1 / 2 * (x ^ 2 / 2 * (1 / 2) ^ n)"
avigad@16959
    93
      apply (rule mult_left_mono)
wenzelm@41550
    94
      apply (rule c)
avigad@16959
    95
      apply simp
avigad@16959
    96
      done
avigad@16959
    97
    also have "... = x ^ 2 / 2 * (1 / 2 * (1 / 2) ^ n)"
avigad@16959
    98
      by auto
avigad@16959
    99
    also have "(1::real) / 2 * (1 / 2) ^ n = (1 / 2) ^ (Suc n)"
huffman@30273
   100
      by (rule power_Suc [THEN sym])
avigad@16959
   101
    finally show ?thesis .
avigad@16959
   102
  qed
avigad@16959
   103
qed
avigad@16959
   104
huffman@20692
   105
lemma aux2: "(%n. (x::real) ^ 2 / 2 * (1 / 2) ^ n) sums x^2"
avigad@16959
   106
proof -
huffman@20692
   107
  have "(%n. (1 / 2::real)^n) sums (1 / (1 - (1/2)))"
avigad@16959
   108
    apply (rule geometric_sums)
huffman@22998
   109
    by (simp add: abs_less_iff)
avigad@16959
   110
  also have "(1::real) / (1 - 1/2) = 2"
avigad@16959
   111
    by simp
huffman@20692
   112
  finally have "(%n. (1 / 2::real)^n) sums 2" .
avigad@16959
   113
  then have "(%n. x ^ 2 / 2 * (1 / 2) ^ n) sums (x^2 / 2 * 2)"
avigad@16959
   114
    by (rule sums_mult)
avigad@16959
   115
  also have "x^2 / 2 * 2 = x^2"
avigad@16959
   116
    by simp
avigad@16959
   117
  finally show ?thesis .
avigad@16959
   118
qed
avigad@16959
   119
huffman@23114
   120
lemma exp_bound: "0 <= (x::real) ==> x <= 1 ==> exp x <= 1 + x + x^2"
avigad@16959
   121
proof -
avigad@16959
   122
  assume a: "0 <= x"
avigad@16959
   123
  assume b: "x <= 1"
nipkow@40864
   124
  have c: "exp x = 1 + x + suminf (%n. inverse(fact (n+2)) * 
avigad@16959
   125
      (x ^ (n+2)))"
avigad@16959
   126
    by (rule exp_first_two_terms)
nipkow@40864
   127
  moreover have "suminf (%n. inverse(fact (n+2)) * (x ^ (n+2))) <= x^2"
avigad@16959
   128
  proof -
nipkow@40864
   129
    have "suminf (%n. inverse(fact (n+2)) * (x ^ (n+2))) <=
avigad@16959
   130
        suminf (%n. (x^2/2) * ((1/2)^n))"
avigad@16959
   131
      apply (rule summable_le)
wenzelm@41550
   132
      apply (auto simp only: aux1 a b)
avigad@16959
   133
      apply (rule exp_tail_after_first_two_terms_summable)
avigad@16959
   134
      by (rule sums_summable, rule aux2)  
avigad@16959
   135
    also have "... = x^2"
avigad@16959
   136
      by (rule sums_unique [THEN sym], rule aux2)
avigad@16959
   137
    finally show ?thesis .
avigad@16959
   138
  qed
avigad@16959
   139
  ultimately show ?thesis
avigad@16959
   140
    by auto
avigad@16959
   141
qed
avigad@16959
   142
huffman@23114
   143
lemma aux4: "0 <= (x::real) ==> x <= 1 ==> exp (x - x^2) <= 1 + x" 
avigad@16959
   144
proof -
avigad@16959
   145
  assume a: "0 <= x" and b: "x <= 1"
avigad@16959
   146
  have "exp (x - x^2) = exp x / exp (x^2)"
avigad@16959
   147
    by (rule exp_diff)
avigad@16959
   148
  also have "... <= (1 + x + x^2) / exp (x ^2)"
avigad@16959
   149
    apply (rule divide_right_mono) 
avigad@16959
   150
    apply (rule exp_bound)
avigad@16959
   151
    apply (rule a, rule b)
avigad@16959
   152
    apply simp
avigad@16959
   153
    done
avigad@16959
   154
  also have "... <= (1 + x + x^2) / (1 + x^2)"
avigad@16959
   155
    apply (rule divide_left_mono)
avigad@17013
   156
    apply (auto simp add: exp_ge_add_one_self_aux)
avigad@16959
   157
    apply (rule add_nonneg_nonneg)
wenzelm@41550
   158
    using a apply auto
avigad@16959
   159
    apply (rule mult_pos_pos)
avigad@16959
   160
    apply auto
avigad@16959
   161
    apply (rule add_pos_nonneg)
avigad@16959
   162
    apply auto
avigad@16959
   163
    done
avigad@16959
   164
  also from a have "... <= 1 + x"
wenzelm@41550
   165
    by (simp add: field_simps zero_compare_simps)
avigad@16959
   166
  finally show ?thesis .
avigad@16959
   167
qed
avigad@16959
   168
avigad@16959
   169
lemma ln_one_plus_pos_lower_bound: "0 <= x ==> x <= 1 ==> 
avigad@16959
   170
    x - x^2 <= ln (1 + x)"
avigad@16959
   171
proof -
avigad@16959
   172
  assume a: "0 <= x" and b: "x <= 1"
avigad@16959
   173
  then have "exp (x - x^2) <= 1 + x"
avigad@16959
   174
    by (rule aux4)
avigad@16959
   175
  also have "... = exp (ln (1 + x))"
avigad@16959
   176
  proof -
avigad@16959
   177
    from a have "0 < 1 + x" by auto
avigad@16959
   178
    thus ?thesis
avigad@16959
   179
      by (auto simp only: exp_ln_iff [THEN sym])
avigad@16959
   180
  qed
avigad@16959
   181
  finally have "exp (x - x ^ 2) <= exp (ln (1 + x))" .
avigad@16959
   182
  thus ?thesis by (auto simp only: exp_le_cancel_iff)
avigad@16959
   183
qed
avigad@16959
   184
avigad@16959
   185
lemma ln_one_minus_pos_upper_bound: "0 <= x ==> x < 1 ==> ln (1 - x) <= - x"
avigad@16959
   186
proof -
avigad@16959
   187
  assume a: "0 <= (x::real)" and b: "x < 1"
avigad@16959
   188
  have "(1 - x) * (1 + x + x^2) = (1 - x^3)"
nipkow@29667
   189
    by (simp add: algebra_simps power2_eq_square power3_eq_cube)
avigad@16959
   190
  also have "... <= 1"
nipkow@25875
   191
    by (auto simp add: a)
avigad@16959
   192
  finally have "(1 - x) * (1 + x + x ^ 2) <= 1" .
avigad@16959
   193
  moreover have "0 < 1 + x + x^2"
avigad@16959
   194
    apply (rule add_pos_nonneg)
wenzelm@41550
   195
    using a apply auto
avigad@16959
   196
    done
avigad@16959
   197
  ultimately have "1 - x <= 1 / (1 + x + x^2)"
avigad@16959
   198
    by (elim mult_imp_le_div_pos)
avigad@16959
   199
  also have "... <= 1 / exp x"
avigad@16959
   200
    apply (rule divide_left_mono)
avigad@16959
   201
    apply (rule exp_bound, rule a)
wenzelm@41550
   202
    using a b apply auto
avigad@16959
   203
    apply (rule mult_pos_pos)
avigad@16959
   204
    apply (rule add_pos_nonneg)
avigad@16959
   205
    apply auto
avigad@16959
   206
    done
avigad@16959
   207
  also have "... = exp (-x)"
huffman@36777
   208
    by (auto simp add: exp_minus divide_inverse)
avigad@16959
   209
  finally have "1 - x <= exp (- x)" .
avigad@16959
   210
  also have "1 - x = exp (ln (1 - x))"
avigad@16959
   211
  proof -
avigad@16959
   212
    have "0 < 1 - x"
avigad@16959
   213
      by (insert b, auto)
avigad@16959
   214
    thus ?thesis
avigad@16959
   215
      by (auto simp only: exp_ln_iff [THEN sym])
avigad@16959
   216
  qed
avigad@16959
   217
  finally have "exp (ln (1 - x)) <= exp (- x)" .
avigad@16959
   218
  thus ?thesis by (auto simp only: exp_le_cancel_iff)
avigad@16959
   219
qed
avigad@16959
   220
avigad@16959
   221
lemma aux5: "x < 1 ==> ln(1 - x) = - ln(1 + x / (1 - x))"
avigad@16959
   222
proof -
avigad@16959
   223
  assume a: "x < 1"
avigad@16959
   224
  have "ln(1 - x) = - ln(1 / (1 - x))"
avigad@16959
   225
  proof -
avigad@16959
   226
    have "ln(1 - x) = - (- ln (1 - x))"
avigad@16959
   227
      by auto
avigad@16959
   228
    also have "- ln(1 - x) = ln 1 - ln(1 - x)"
avigad@16959
   229
      by simp
avigad@16959
   230
    also have "... = ln(1 / (1 - x))"
avigad@16959
   231
      apply (rule ln_div [THEN sym])
avigad@16959
   232
      by (insert a, auto)
avigad@16959
   233
    finally show ?thesis .
avigad@16959
   234
  qed
nipkow@23482
   235
  also have " 1 / (1 - x) = 1 + x / (1 - x)" using a by(simp add:field_simps)
avigad@16959
   236
  finally show ?thesis .
avigad@16959
   237
qed
avigad@16959
   238
avigad@16959
   239
lemma ln_one_minus_pos_lower_bound: "0 <= x ==> x <= (1 / 2) ==> 
avigad@16959
   240
    - x - 2 * x^2 <= ln (1 - x)"
avigad@16959
   241
proof -
avigad@16959
   242
  assume a: "0 <= x" and b: "x <= (1 / 2)"
avigad@16959
   243
  from b have c: "x < 1"
avigad@16959
   244
    by auto
avigad@16959
   245
  then have "ln (1 - x) = - ln (1 + x / (1 - x))"
avigad@16959
   246
    by (rule aux5)
avigad@16959
   247
  also have "- (x / (1 - x)) <= ..."
avigad@16959
   248
  proof - 
avigad@16959
   249
    have "ln (1 + x / (1 - x)) <= x / (1 - x)"
avigad@16959
   250
      apply (rule ln_add_one_self_le_self)
avigad@16959
   251
      apply (rule divide_nonneg_pos)
avigad@16959
   252
      by (insert a c, auto) 
avigad@16959
   253
    thus ?thesis
avigad@16959
   254
      by auto
avigad@16959
   255
  qed
avigad@16959
   256
  also have "- (x / (1 - x)) = -x / (1 - x)"
avigad@16959
   257
    by auto
avigad@16959
   258
  finally have d: "- x / (1 - x) <= ln (1 - x)" .
wenzelm@41550
   259
  have "0 < 1 - x" using a b by simp
nipkow@23482
   260
  hence e: "-x - 2 * x^2 <= - x / (1 - x)"
wenzelm@41550
   261
    using mult_right_le_one_le[of "x*x" "2*x"] a b
wenzelm@41550
   262
    by (simp add:field_simps power2_eq_square)
avigad@16959
   263
  from e d show "- x - 2 * x^2 <= ln (1 - x)"
avigad@16959
   264
    by (rule order_trans)
avigad@16959
   265
qed
avigad@16959
   266
huffman@23114
   267
lemma exp_ge_add_one_self [simp]: "1 + (x::real) <= exp x"
avigad@16959
   268
  apply (case_tac "0 <= x")
avigad@17013
   269
  apply (erule exp_ge_add_one_self_aux)
avigad@16959
   270
  apply (case_tac "x <= -1")
avigad@16959
   271
  apply (subgoal_tac "1 + x <= 0")
avigad@16959
   272
  apply (erule order_trans)
avigad@16959
   273
  apply simp
avigad@16959
   274
  apply simp
avigad@16959
   275
  apply (subgoal_tac "1 + x = exp(ln (1 + x))")
avigad@16959
   276
  apply (erule ssubst)
avigad@16959
   277
  apply (subst exp_le_cancel_iff)
avigad@16959
   278
  apply (subgoal_tac "ln (1 - (- x)) <= - (- x)")
avigad@16959
   279
  apply simp
avigad@16959
   280
  apply (rule ln_one_minus_pos_upper_bound) 
avigad@16959
   281
  apply auto
avigad@16959
   282
done
avigad@16959
   283
avigad@16959
   284
lemma ln_add_one_self_le_self2: "-1 < x ==> ln(1 + x) <= x"
avigad@16959
   285
  apply (subgoal_tac "x = ln (exp x)")
avigad@16959
   286
  apply (erule ssubst)back
avigad@16959
   287
  apply (subst ln_le_cancel_iff)
avigad@16959
   288
  apply auto
avigad@16959
   289
done
avigad@16959
   290
avigad@16959
   291
lemma abs_ln_one_plus_x_minus_x_bound_nonneg:
avigad@16959
   292
    "0 <= x ==> x <= 1 ==> abs(ln (1 + x) - x) <= x^2"
avigad@16959
   293
proof -
huffman@23441
   294
  assume x: "0 <= x"
wenzelm@41550
   295
  assume x1: "x <= 1"
huffman@23441
   296
  from x have "ln (1 + x) <= x"
avigad@16959
   297
    by (rule ln_add_one_self_le_self)
avigad@16959
   298
  then have "ln (1 + x) - x <= 0" 
avigad@16959
   299
    by simp
avigad@16959
   300
  then have "abs(ln(1 + x) - x) = - (ln(1 + x) - x)"
avigad@16959
   301
    by (rule abs_of_nonpos)
avigad@16959
   302
  also have "... = x - ln (1 + x)" 
avigad@16959
   303
    by simp
avigad@16959
   304
  also have "... <= x^2"
avigad@16959
   305
  proof -
wenzelm@41550
   306
    from x x1 have "x - x^2 <= ln (1 + x)"
avigad@16959
   307
      by (intro ln_one_plus_pos_lower_bound)
avigad@16959
   308
    thus ?thesis
avigad@16959
   309
      by simp
avigad@16959
   310
  qed
avigad@16959
   311
  finally show ?thesis .
avigad@16959
   312
qed
avigad@16959
   313
avigad@16959
   314
lemma abs_ln_one_plus_x_minus_x_bound_nonpos:
avigad@16959
   315
    "-(1 / 2) <= x ==> x <= 0 ==> abs(ln (1 + x) - x) <= 2 * x^2"
avigad@16959
   316
proof -
wenzelm@41550
   317
  assume a: "-(1 / 2) <= x"
wenzelm@41550
   318
  assume b: "x <= 0"
avigad@16959
   319
  have "abs(ln (1 + x) - x) = x - ln(1 - (-x))" 
avigad@16959
   320
    apply (subst abs_of_nonpos)
avigad@16959
   321
    apply simp
avigad@16959
   322
    apply (rule ln_add_one_self_le_self2)
wenzelm@41550
   323
    using a apply auto
avigad@16959
   324
    done
avigad@16959
   325
  also have "... <= 2 * x^2"
avigad@16959
   326
    apply (subgoal_tac "- (-x) - 2 * (-x)^2 <= ln (1 - (-x))")
nipkow@29667
   327
    apply (simp add: algebra_simps)
avigad@16959
   328
    apply (rule ln_one_minus_pos_lower_bound)
wenzelm@41550
   329
    using a b apply auto
nipkow@29667
   330
    done
avigad@16959
   331
  finally show ?thesis .
avigad@16959
   332
qed
avigad@16959
   333
avigad@16959
   334
lemma abs_ln_one_plus_x_minus_x_bound:
avigad@16959
   335
    "abs x <= 1 / 2 ==> abs(ln (1 + x) - x) <= 2 * x^2"
avigad@16959
   336
  apply (case_tac "0 <= x")
avigad@16959
   337
  apply (rule order_trans)
avigad@16959
   338
  apply (rule abs_ln_one_plus_x_minus_x_bound_nonneg)
avigad@16959
   339
  apply auto
avigad@16959
   340
  apply (rule abs_ln_one_plus_x_minus_x_bound_nonpos)
avigad@16959
   341
  apply auto
avigad@16959
   342
done
avigad@16959
   343
avigad@16959
   344
lemma ln_x_over_x_mono: "exp 1 <= x ==> x <= y ==> (ln y / y) <= (ln x / x)"  
avigad@16959
   345
proof -
wenzelm@41550
   346
  assume x: "exp 1 <= x" "x <= y"
avigad@16959
   347
  have a: "0 < x" and b: "0 < y"
wenzelm@41550
   348
    apply (insert x)
huffman@23114
   349
    apply (subgoal_tac "0 < exp (1::real)")
avigad@16959
   350
    apply arith
avigad@16959
   351
    apply auto
huffman@23114
   352
    apply (subgoal_tac "0 < exp (1::real)")
avigad@16959
   353
    apply arith
avigad@16959
   354
    apply auto
avigad@16959
   355
    done
avigad@16959
   356
  have "x * ln y - x * ln x = x * (ln y - ln x)"
nipkow@29667
   357
    by (simp add: algebra_simps)
avigad@16959
   358
  also have "... = x * ln(y / x)"
avigad@16959
   359
    apply (subst ln_div)
avigad@16959
   360
    apply (rule b, rule a, rule refl)
avigad@16959
   361
    done
avigad@16959
   362
  also have "y / x = (x + (y - x)) / x"
avigad@16959
   363
    by simp
wenzelm@41550
   364
  also have "... = 1 + (y - x) / x" using x a by (simp add: field_simps)
avigad@16959
   365
  also have "x * ln(1 + (y - x) / x) <= x * ((y - x) / x)"
avigad@16959
   366
    apply (rule mult_left_mono)
avigad@16959
   367
    apply (rule ln_add_one_self_le_self)
avigad@16959
   368
    apply (rule divide_nonneg_pos)
wenzelm@41550
   369
    using x a apply simp_all
avigad@16959
   370
    done
nipkow@23482
   371
  also have "... = y - x" using a by simp
nipkow@23482
   372
  also have "... = (y - x) * ln (exp 1)" by simp
avigad@16959
   373
  also have "... <= (y - x) * ln x"
avigad@16959
   374
    apply (rule mult_left_mono)
avigad@16959
   375
    apply (subst ln_le_cancel_iff)
avigad@16959
   376
    apply force
avigad@16959
   377
    apply (rule a)
wenzelm@41550
   378
    apply (rule x)
wenzelm@41550
   379
    using x apply simp
avigad@16959
   380
    done
avigad@16959
   381
  also have "... = y * ln x - x * ln x"
avigad@16959
   382
    by (rule left_diff_distrib)
avigad@16959
   383
  finally have "x * ln y <= y * ln x"
avigad@16959
   384
    by arith
wenzelm@41550
   385
  then have "ln y <= (y * ln x) / x" using a by (simp add: field_simps)
wenzelm@41550
   386
  also have "... = y * (ln x / x)" by simp
wenzelm@41550
   387
  finally show ?thesis using b by (simp add: field_simps)
avigad@16959
   388
qed
avigad@16959
   389
avigad@16959
   390
end